Clays and Clay Minerals, Vol. 59, No. 5, 478–489, 2011. - Hong, Hanlie; Xie, Shucheng; Lai, Xulong (My University, 2011)
In order to better understand the provenance of the sediments and environmental change associated with the Permian-Triassic (P/T) biotic crisis, a comparative clay mineralogical study of the Permian-Triassic boundary (PTB) sediments between the Meishan section (the Global Stratotype Section and Point of the PTB) and the Xiakou section, southern China, was undertaken using X-ray diffraction and differential scanning calorimetry (DSC). The results showed that clay minerals of the packstone bed 24e, in which the preludial mass extinction occurred at Meishan, consist of 56% mixed-layer illite-smectite (I-S), 39% illite, and 5% kaolinite. A dehydroxylation effect was measured at 652ºC, indicating that I-S and illite of this bed contain mainly cis-vacant (cv) layers related to volcanic origin. The dehydroxylation event correlates with bed P257 at Xiakou. The white clay bed 25 also corresponding to the main extinction event at Meishan contains 95% I-S and 5% kaolinite, with a strong endothermic effect at 676ºC and a weaker one at 514ºC in the DSC curve. These results are attributed to dehydroxylation of cv layers in I-S clays, suggesting that I-S in the white clay bed was derived from marine alteration of volcanic ash, in agreement with the conodont-correlated clay (P258) at Xiakou. (Conodonts are tooth-like microfossils and are usually used as an indicator of age in PTB stratigraphy.) Increases in chlorite and illite contents in the black clays (bed 26) at Meishan and the conodont-correlated black clay layer (P259b) at Xiakou probably indicate stronger erosional processes under cooler and more arid conditions. Volcanic materials found in a bed which marked the prelude to the main episode of mass extinction reinforce the temporal link between volcanism and the mass extinction.
Volcanism In Association With The Prelude To Mass Extinction And Environment Change Across The Permian-triassic Boundary (ptb), Southern China
gsccm59505-hon.pdf-- 538KB
Keywords: Periodicals; Geology; Mixed-layer Illite-smectite (I-S) Clays; Permian-Triassic Boundary (PTB); Preludial Mass Extinction; Volcanism